Censorship in Romania - Vianu, Lidia (Central European University Press, 1998)
Through a series of interviews with prominent Romanian literary figures and a select presentation of their writings, Lidia Vianu asks how, under communism, did Romanian writers cope with constant ideological shifts and, in turn, respond to the censorship that so often accompanied such changes? Now that Romania has emerged from almost fifty years of Communist rule, what is the current status of censorship? These writers are important because, though working under the terror of communism, they dared to put their thoughts into writing, remaining true to their craft, and, in some instances, even arranging for publication. Vianu has chosen a series of subversive writings that not only indicted communism but were also widely embraced by the Romanian public. The author continues to argue that after the fall of communism and the disappearance of subversive literature, the Romanian public started to devour works of translation. A somewhat different form of censorship arose: state-sponsored censorship was replaced by what Vianu terms a crisis of native writing.